A decade of molecular cell atlases. Issue 8 (August 2022) - Quake, Stephen R.
Abstract : In recent years there has been tremendous progress towards deep molecular characterization of cell types using single-cell transcriptome sequencing, creating so-called 'cell atlases'. These atlases provide a basic understanding of how different cell types of the same organism – which all share the genome – make distinct use of subsets of genes from the genome to create a variety of distinct cell types across tissues with specialized functions. In this opinion article I discuss some of the history and technological innovations that led to the development of whole-organism atlases. Highlights: The development of molecular cell atlases has been crucially dependent on technological advances, which can be traced back three decades. Important technologies include the development of single-cell cDNA libraries, whole-transcriptome analysis such as next-generation sequencing, and microfluidic tools that enable high-throughput cell processing. A vibrant international community has made important scientific contributions with the use of these tools to discover and characterize cell types over an extended period, starting around 2011–2012. Whole-organism cell atlases are now reaching fruition for a number of important species, including human, and they serve as phenotypic companions to the genome for these animals.